2011
DOI: 10.1590/s1516-35982011000600010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of diets for quails with vitamins A, D and E on performance of the birds and quality and enrichment of eggs

Abstract: -The objective of this research was to evaluate the performance of birds and the quality and enrichment of eggs from quails fed diets supplemented with vitamins A, D and E. Three experiments were performed, one for each vitamin, under completely randomized experimental design, with six replicates and eight birds per plot, totaling 192 quails. Performance of birds was evaluated by the daily feed intake, egg weight, laying percentage (%) and food conversion, per kg and dozen of eggs. It was also evaluated the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
2
6
1
1
Order By: Relevance
“…Indeed, the synergistic action resulting from the association of several protein sources in the A3 food has already been demonstrated by many researchers including Smith [33] who showed that various protein sources lead to better performance of spawn subjects. The daily egg laying rates obtained in quails in this study are lower than those obtained by Marques et al [34], Berto et al [35], Hassan [36] and Abdel-Azeem [30]. who worked respectively on quails during a period ranging from the 6 th to the 14 th week.…”
Section: Discussioncontrasting
confidence: 79%
“…Indeed, the synergistic action resulting from the association of several protein sources in the A3 food has already been demonstrated by many researchers including Smith [33] who showed that various protein sources lead to better performance of spawn subjects. The daily egg laying rates obtained in quails in this study are lower than those obtained by Marques et al [34], Berto et al [35], Hassan [36] and Abdel-Azeem [30]. who worked respectively on quails during a period ranging from the 6 th to the 14 th week.…”
Section: Discussioncontrasting
confidence: 79%
“…No significant (P>0.05) effects due to vitamin A on FCR on the periods of 7-14, 7-21 and 7-28 days of age. Vitamin A supplementation did not result in statistical difference for FCR of quails during the experimental period (Marques et al, 2011). Similar results with vitamin A supplementation were described by Lin et al (2002) andMendonça Júnior et al (2002), who also did not verify any differences on FCR of hens supplied with vitamin A supplementation.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 87%
“…In the last four days of the trial, 12 eggs of each replicate were collected and sent to the laboratory for Selenium and vitamin E determinations. For micronutrients analysis, high-performance liquid chromatography (HPLC) was employed, according to Marques et al (2011).…”
Section: Methodsmentioning
confidence: 99%